Perbandingan Perbaikan Citra Magnetic Resonance Imaging (MRI) Menggunakan Ruang Warna RGB, HSV dan YCbCr Dengan Metode Histogram Equalization dan Contrast Streching - Hamzah, Fahmi Aliefuddin; Wahyusari, Retno (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2023)
Magnetic resonance imaging (MRI) images are the images most often used in the field of radiology. Some of the problems that often occur in medical images are the scanning results that have decreased quality due to noise factors. MRI images that have been printed and then entered into a computerized system will experience a decrease in quality such as the image looks blurry or dark. So it is necessary to improve image quality to create a quality image in order to make it easier for doctors to diagnose and reduce the possibility of analysis errors. Image enhancement (IE) techniques are widely applied to image processing to increase the probability of success in image analysis. Image improvement methods include Histogram Equalization (HE) and Contrast Streching (CS). One of the good images can be seen from the MSE value which is the smallest or close to zero and the highest PSNR value. The color space has an effect on image improvement and can be included in the pre-processing process including RGB, HSV, and YCbCr. Based on the 100 images tested, the results of the RGB image enhancement by 31%, 66% HSV, and 27% YCbCr were said to be successful with the Histogram equalization and contrast streching methods, so the HSV color space is superior to the RGB and YCbCr color spaces.